2021
DOI: 10.3201/eid2704.203859
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza Clade 2.3.4.4 Subtype H5N6 Viruses Isolated from Wild Whooper Swans, Mongolia, 2020

Abstract: We identified clade 2.3.4.4 highly pathogenic avian influenza A(H5N6) viruses from whooper swans ( Cygnus cygnus ) found dead in Mongolia. The identification of these infections in wild birds in this area is of concern because of the potential for virus dissemination during fall migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…These migration patterns and our tMRCA data of A/wildDuck/MN/H5N6/2018-19 (July to September 2018) hypothesize that these migratory waterfowl pick up H5N6 viruses during their spring migration, and carry it to their breeding ground in Mongolia where they stay between May and August. This was consistent with a previous study that suggested that the spring bird migration pattern matched with the timing and route of H5N6 virus transmission between Xinjiang and Mongolia [ 15 ]. Taken together, this data suggests that the spring migration plays a significant role in the transmission and circulation of HPAI H5N6 in Mongolia.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These migration patterns and our tMRCA data of A/wildDuck/MN/H5N6/2018-19 (July to September 2018) hypothesize that these migratory waterfowl pick up H5N6 viruses during their spring migration, and carry it to their breeding ground in Mongolia where they stay between May and August. This was consistent with a previous study that suggested that the spring bird migration pattern matched with the timing and route of H5N6 virus transmission between Xinjiang and Mongolia [ 15 ]. Taken together, this data suggests that the spring migration plays a significant role in the transmission and circulation of HPAI H5N6 in Mongolia.…”
Section: Discussionsupporting
confidence: 92%
“…This result does corroborate our molecular characterization which showed that the A/wildDuck/MN/H5N6/2018-19 isolate lacked two of the individual mutations in the PB2 protein (lysine at position 627 to glutamic acid and aspartate at position 701 to asparagine) leading to low pathogenicity in mice [ 52 , 56 ]. However, the A/wildDuck/MN/H5N6/2018-19 isolate MLD 50 value (5.68-log10 EID50) was lower than the MLD 50 (6.38-log 10 EID 50 ) of the A (H5N6) Xinjiang/2020/2.3.4.4 h virus identified in China in 2020, despite its close relationship with the recently described 2020 H5N6 Mongolian isolates [ 15 , 17 ]. This suggests that the potential virulence of the A/wildDuck/MN/H5N6/2018-19 isolates are likely to be higher than the 2020 H5N6 Mongolian isolates.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations